Research and development of welding methods and welding mechanism of high-entropy alloys: A review. (September 2021) - Zhang, Yali; Jiang, Xiaosong; Fang, Yan; Fang, Yongjian; Liu, Bing; Sun, Hongliang; Shao, Zhenyi; Song, Tingfeng
Abstract: In this paper, the solid-state welding and fusion welding of high-entropy alloys (HEAs) were reviewed. For solid-state welding of HEAs, the influence of microstructure change and welding parameters on properties of welded joints were discussed. For fusion welding of HEAs, the application of laser welding, electron beam welding and gas tungsten arc welding was analyzed. Then relevant welding mechanisms, solidification behavior of grains, and phase formation in fusion welding of HEAs were discussed. The methods optimizing properties and microstructure of welded joints were discussed, including the adjustment of parameters, usage of pre-welding heat treatment and post-welding heat treatment, as well as the application of metallic interlayers in dissimilar welding of HEAs. The application of numerical simulation in HEAs welding could facilitate the optimization of experimental parameters. In addition, HEAs have been applied as coatings to improve the properties and life of materials based on welding methods, and the application of HEAs fillers in welding was also achieved. In the future, molecular dynamics simulation can be applied to analyze the atomic diffusion and stress distribution in HEAs welding, and there are still many aspects that need to be explored in the field of HEAs welding.